An experimental investigation on the hydraulic behavior of declining rate filtration - AKGİRAY, ÖMER (TAYLOR & FRANCIS INC, 2013)
Hydraulic behavior of declining rate filtration (DRF) was investigated by means of pilot-scale experiments. A bank of four declining rate filters was constructed and operated. The common water level in the filters, individual filter velocities, and head losses in the filters were carefully monitored and recorded as functions of time. Many of the previous studies on DRF employed either a single average filtration velocity or a single coagulant dosage. In this study, however, filter runs were repeated treating the same water at several different filtration rates and coagulant dosages. Using such an experimental matrix of several different rates and coagulant dosages allowed an evaluation of the behavior of the declining rate filtration system under different operating conditions and the effects of the mentioned variables on various hydraulic characteristics of the DRF system. The validity of certain simplifying assumptions used in design calculations was also tested in these experiments. It is believed that the new data presented herein will lead to a better understanding of DRF.
Keywords: Constant rate filtration; Declining rate filtration; Filtration; Water treatment; BANK OPERATION; CONSTANT-RATE; RATE FILTERS; DESIGN